Analysis of sports performance as a dynamical system by means of the relative phase - Walter, F.; Lames, M.; McGarry, T. (International Journal of Computer Science in Sport, 2007)
The notion of relative phases plays an important role in synergetic approaches to movement science. Coordinative patterns between the movements of several limbs within a person (Kelso, 1995) for example, can be characterized by means of the relative phase. Additionally, there are various successful attempts to utilize the cognition of dynamical systems to analyse coordinated interpersonal behaviour (Schmidt, et al. 1990). It is a broadly accepted fact that the theory of dynamical systems helps to deal with the degrees of freedom (Bernstein) problem and that the notion of relative phase is fit to describe and explain the patterns that emerge from coordinated behaviour. But, as all the variables of a complex system are being reduced to one essential - collective - variable (i.e. order parameter), which constitutes its' behaviour, one has to be very precise with the choice of this variable. This paper wants to shed light on the potential - but also on the challenges - of a dynamical system's analysis with relative phase measurement of interaction phenomena in (dyadic) game sports.